Interpretational Circle as the Key Principle of the Philological Investigations of William Shakespeare’s Non-Dramatic Texts - A. A. Lipgart (Дискурс профессиональной коммуникации, 2023)
Scholars engaged in the Shakespeare studies are familiar with the common problem arising in such kind of investigations – that of the insufficiency of the information concerning the biography of the great writer, the textual history of his works, the intended meaning of some of his texts. As the present research shows, in contrast to Shakespeare’s dramatic texts whose biographical interpretations are largely unreliable, his non-dramatic works provide rich material for further biographical interpretations, these latter in their turn enabling the reader to come to a better understanding of texts under discussion. The present study is aimed at proving that the right approach to interpreting Shakespeare’s non-dramatic works consists in moving within a kind of interpretational circle: after gathering the initial information about the content of a text and the more general context in which it was created, after realizing the objective limitations of a biographical approach to each particular text, a scholar may pass on to carefully extracting from a non-dramatic work by Shakespeare the information which may be treated as biographically and historically relevant.The analysis carried out in the paper has shown that Shakespeare’s sonnets are the most fruitful material for gathering biographical information and that the interpretation of the texts of the sonnets as such does not require any profound knowledge of the general historical and cultural context, while the text of “The Phoenix and the Turtle” cannot be understood without taking recourse to the widest imaginable historical and cultural information; Shakespeare’s narrative poems “Venus and Adonis” and “The Rape of Lucrece” may be placed in-between these two extremes.